COVID-19 induced change in higher education: Reflections on rapidly transitioning a first-year undergraduate academic literacies unit from face-to-face to online - Grimmer, Raelke; Pollard, Andrew; Rolls, Nicola (Journal of Academic Language and Learning, 2020)
The COVID-19 pandemic forced many Australian universities to move all face-to-face teaching online partway through Semester 1, 2020. This rapid shift in teaching mode presented not only pedagogical challenges, but challenges in how best to support staff and students across this transition. In this paper, three academic foundations lecturers teaching an undergraduate academic literacies unit at a regional Australian university reflect on their experiences in moving the unit online four weeks into the semester. The student cohort consisted of high numbers of non-traditional students and students who did not necessarily have access to the technology and equipment they needed to learn online. While the transition presented challenges, working to resolve and adapt to the challenges also presented opportunities to experiment with online learning technology and develop skills and strategies to implement for future cohorts of online students. As the higher education sector continues to experience rapid change, it is imperative to continue to develop strategies to support students in their learning during these uncertain times.